Plutarch und die Evangelien Von der Gattungskritik zum interkulturellen Vergleich - Staub, David A. (Mohr Siebeck, 2025)
In the exegetical literature, Plutarchs Parallel Lives are often used as comparative texts for the Gospels. But how can and should the comparison between the Gospels and the Vitae be carried out, and what benefits can be gained from it? In an examination of the research debate on the genre affiliation of the Gospels, David Staub develops his own approach, which he presents and tests using a comparison between Plutarchs Life of Numa and the Gospel of Luke as an example.
PublicationDate: 20250530
Keywords: Neues Testament -- Religionsgeschichte -- Komparatistik -- Biographik -- Frühe Kaiserzeit -- Antike